Etiology of Pediatric Stroke at a Tertiary Care Hospital of Southern Punjab - Tariq, Ali; Hussain, Fayyaz; Rahman, Ikram Ur; Safdar, Sohail (Biological and Clinical Sciences Research Journal, 2025)
Pediatric stroke is an important cause of childhood morbidity with diverse etiological factors that vary across regions. Early identification of underlying causes is essential for timely management and improved outcomes. Objective: To determine the pattern and burden of etiological factors of pediatric stroke at a tertiary care hospital in Southern Punjab. Methods: This descriptive case series was conducted in the Department of Neurology, The Children's Hospital and Institute of the Child Health, Multan, and included 110 children diagnosed with stroke using a non-probability purposive sampling technique. After enrollment, detailed history-taking and thorough clinical examination were performed, followed by appropriate neurological and laboratory investigations to ascertain the aetiology of the stroke. Demographic variables, stroke type, and etiological factors were recorded. Data were analysed using SPSS version 23. Mean and standard deviation were calculated for continuous variables such as age and weight. At the same time, frequencies and percentages were computed for categorical variables, including gender, age groups, residential status, stroke type, and etiological factors. Results: Out of 110 children, 65.5% were males and 34.5% were females, with a mean age of 5.85 ± 2.64 years. Most patients (72.7%) were aged six years or younger. The majority lived in urban areas (70.0%) and were from middle-income families (73.6%). Ischemic stroke was observed in 83.6% of cases, whereas 16.4% had hemorrhagic stroke. The mean body weight was 14.93 ± 4.87 kg, and obesity was noted in 13.6% of children. Infective causes were the most frequent etiological factor (50.9%), followed by vascular (26.4%), haematological (12.7%), cardiac (4.5%), and unknown causes (5.5%). Conclusion: Intracranial infections were the leading etiological factor of pediatric stroke in this setting, followed by vascular and haematological causes. Ischemic stroke was more prevalent than hemorrhagic stroke. Awareness of these patterns may facilitate early Diagnosis, targeted management, and improved prognosis in children with stroke.